Application of Think Talk Write (TTW) Model Assisted by Geogebra to Improve Student’s Ability of Mathematical Concept Understanding in Class X of MAS PAB 2 Helvetia - Ummu Habibah Hadi Kesuma; Dian Armanto (Asian Journal of Applied Education (AJAE), 2023)
The purpose of this study was to improve students' ability to understand mathematical concepts by applying Think Talk Write (TTW) using GeoGebra in class X MAS PAB 2 Helvetia in the 2022/2023 school year. The subjects were 36 students of class X MIA 1 MAS PAB 2 Helvetia. Data collection techniques used are teacher observation sheets, mathematical Concept Understanding ability tests, and documentation. Researcher used type of classroom action research (CAR). Preliminary tests result obtained 5 students (13.89%) completed with an average of 53,99% (lower). In the tests cycle I, 4 students (44,4%) completed with an average of 64,40% (low). In the test cycle II, 33 students (91,67%) were completed with an average of 88,02% (high). It can be concluded that the application of Think Talk Write (TTW) using GeoGebra can improve the ability to understand mathematical concepts of class X MAS PAB 2 Helvetia students